PENERAPAN KEBIJAKAN PENENGGELAMAN DAN PELEDAKKAN KAPAL ILLEGAL FISHING PADA MASA KEPEMIMPINAN PRESIDEN JOKO WIDODO - Siti Avianty Yuniarsih (HI 16 UMY 75, 2016)
This journal explains about why Indonesia implement a policy about sinking and blowing up of the foreign boats under President Joko Widodo era. Sinking and blowing up of the foreign boats is one of the policy to against illegal fishing. Indonesia lost over $20 billion due to illegal fishing. This is why President Joko Widodo wants to implement the policy to sinking and blowing up the foreign boats to make shock therapy for illegal fishing people.